Komunikasi Pemasaran Smesco Pasca Pandemi Covid-19 (Studi Deskritif Kualitatif) Peluang dan Tantangan Pelaku UMKM Binaan Smesco - Harningsih Harningsih; Delia Putri Anggriani (Cakrawala - Jurnal Humaniora, 2023)
The impact of the COVID-19 virus has hit the health and social sectors hard, with the economic aspect being the most affected. Large-scale social restrictions (PSBB) have been one of the government's policies to curb the spread of the COVID-19 virus, resulting in a slump in micro, small, and medium-sized enterprises (UMKM), with widespread effects on the national economy. This research aims to delve deeper into Smesco Indonesia's efforts to assist UMKM during the COVID-19 pandemic, viewing it as both an opportunity and a challenge to enhance productivity in the wake of the pandemic-induced downturn. Through a qualitative descriptive study using the case study research method, this research comprehensively outlines, explains, and elaborates on Smesco's marketing communication implementation post-pandemic. The research findings indicate that Smesco Indonesia is committed to helping UMKM recover from their slump by providing various services, including sales promotion, marketing, market information, product distribution support, and consultation. They have also organized webinars to educate UMKM and expand their business horizons, not only for offline but also online sales. Smesco hopes that UMKM can elevate their status, which presents opportunities and challenges for business owners. The UMKM upgrading program initiated by Smesco offers several advantages, including the chance for UMKM products to enter the global market and support through product selection for local supermarket markets. The requirements for UMKM upgrading are relatively simple, such as having the necessary business legality documents like the Business Identification Number (NIB) or Limited Liability Company (PT) for medium-sized businesses, Halal certification, and BPOM approval for production.